تطبيق طريقة القراءة في تعلم اللغة العربية في مدرسة إتحاد الإسلامي الثانوية الإسلامية 69 بجاكرتا الشرقية - Noviady, Harry; Hidayat, Taufik (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2025)
ملخص: يهدف هذا البحث إلى وصف تطبيق طريقة القراءة في مدرسة إتحاد الإسلامي الثانوية الإسلامية 69 بجاكرتا الشرقية. ويركز هذا البحث على كيفية تطبيق هذه الطريقة، وإلى تجديد العوامل المؤثرة العوامل في تعلم اللغة العربية لدى الطلاب. استخدم هذا البحث المنهج الوصفي النوعي الميداني، ومجعت البياانت خلال الملاحظة والمقابلة والتوثيق. وشارك في هذا البحث مدير المدرسة، معلم اللغة العربية، والطلاب في مدرسة إتحاد الإسلامي الثانوية الإسلامية 69 بجاكرتا الشرقية. نتائج البحث تظهر أن تطبيق طريقة القراءة له تأثير كبير على الطلاب، خاصة في ثلاثة جوانب رئيسية، وهي الجانب المعرفي (تحسين فهم النص والمفردات)، والجانب العاطفي (تحسين الدافع والثقة بالنفس)، والجانب الحركي (القدرة على القراءة باللفظ والصوت الصحيح). كما نجحت هذه الطريقة في خلق جو تعليمي نشط وتشاركي وحواري في الفصل. أما العوامل التي تؤثر على نجاح طريقة القراءة فتشمل العوامل الداخلية للطالب (الدافع والاستعداد للتعلم)، والعوامل المتعلقة بالمعلم (الكفاءة التربوية وطرق التدريس)، والعوامل المتعلقة بالبيئة ونظام التعلم (دعم المرافق والمناهج الدراسية والمناخ الأكاديمي للمدرسة). وبالتالي، يمكن استنتاج أن طريقة القراءة هي إحدى الطرق المناسبة والفعالة لتطبيقها في تعليم اللغة العربية في بيئة المدارس التابعة لجمعية مدرسة إتحاد الإسلامي الثانوية الإسلامية 69 بجاكرتا الشرقية. ونجاحها يعتمد بشكل كبير على التآزر بين استعداد الطلاب وإبداع المعلمين ودعم المؤسسات التعليمية بشكل شامل. الكلمات الأساسية: طريقة القراءة، تعلم اللغة العربية، مدرسة إتحاد الإسلامي الثانوية الإسلامية 69. Abstract: This research aims to describe the application of the reading method at the Islamic Union Secondary School 69 in East Jakarta. This research focuses on how this method is applied and on renewing the factors that influence students' learning of the Arabic language. This research used a qualitative descriptive field approach, and data was collected through observation, interviews, and documentation. The school principal, Arabic language teacher, and students at the Islamic Union Islamic Secondary School 69 in East Jakarta participated in this research. The results of the research show that the application of the reading method has a significant impact on students, especially in three main aspects, namely the cognitive aspect (improving text and vocabulary comprehension), the emotional aspect (improving motivation and self-confidence), and the motor aspect (the ability to read with correct pronunciation and intonation). This method also succeeded in creating an active, participatory, and interactive learning atmosphere in the classroom. The factors that influence the success of the reading method include internal factors related to the student (motivation and readiness to learn), factors related to the teacher (educational competence and teaching methods), and factors related to the environment and learning system (support from facilities, curricula, and the academic climate of the school). Therefore, it can be concluded that the reading method is one of the appropriate and effective methods to be applied in Arabic language teaching in the schools affiliated with the Islamic Union Secondary School Association 69 in East Jakarta. Its success depends largely on the synergy between student readiness, teacher creativity, and comprehensive support from educational institutions. Keywords: Reading method, learning Arabic, Islamic Union Secondary School 69 Abstrak: Penelitian ini bertujuan untuk menggambarkan penerapan metode membaca di Sekolah Menengah Islam Persatuan Islam 69 Jakarta Timur. Penelitian ini berfokus pada cara penerapan metode tersebut, serta mengidentifikasi faktor-faktor yang mempengaruhi proses pembelajaran bahasa Arab pada siswa. Penelitian ini menggunakan metode deskriptif kualitatif lapangan, dan data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Peserta penelitian meliputi kepala sekolah, guru bahasa Arab, dan siswa di Sekolah Menengah Islam 69 Jakarta Timur. Hasil penelitian menunjukkan bahwa penerapan metode membaca memiliki dampak besar pada siswa, terutama dalam tiga aspek utama, yaitu aspek kognitif (peningkatan pemahaman teks dan kosakata), aspek afektif (peningkatan motivasi dan kepercayaan diri), dan aspek motorik (kemampuan membaca dengan pengucapan dan suara yang benar). Metode ini juga berhasil menciptakan suasana pembelajaran yang aktif, partisipatif, dan dialogis di kelas. Faktor-faktor yang mempengaruhi keberhasilan metode membaca meliputi faktor internal siswa (motivasi dan kesiapan belajar), faktor terkait guru (kompetensi pedagogis dan metode pengajaran), serta faktor terkait lingkungan dan sistem pembelajaran (dukungan fasilitas, kurikulum, dan iklim akademik sekolah). Oleh karena itu, dapat disimpulkan bahwa metode membaca merupakan salah satu metode yang tepat dan efektif untuk diterapkan dalam pengajaran bahasa Arab di lingkungan sekolah-sekolah yang berafiliasi dengan Asosiasi Sekolah Islam Persatuan 69 Jakarta Timur. Kesuksesannya sangat bergantung pada sinergi antara kesiapan siswa, kreativitas guru, dan dukungan lembaga pendidikan secara menyeluruh. Kata kunci: Metode membaca, Pembelajaran bahasa Arab, Sekolah Menengah Islam Ittihad Al-Islami 69